Quantitative ultrasonography (Development in Poland) - FILIPCZYŃSKI, L. (Archives of Acoustics, 1991)
Ultrasonography is based on the component interpretation of ultrasonic images of the patients organ. Factors enabling a correct diagnosis are of qualitative character, mainly, because in the first place they depend on the experience of the specialist performing the examination. However, a necessity of describing certain quantities with numbers appeared already in the early stages of development of ultrasonography. This need becomes more and more apparent and even essential in certain domains of ultrasonography where Doppler techniques are applied.